The Economic Implication of Boko Haram Insurgency in The North East Nigeria - Dominic Aondona Iornumbe; Tanko Shawulu Paul (Jurnal Restorasi : Hukum dan Politik, 2025)
Boko Haram is loosely modelled on the Taliban movement in Afghanistan; one of the groups’ primary bases in Kanama in Yobe state was named Afghanistan before its destruction. The group has also issued statements expressing solidarity with al-Qaeda and has threatened the United States. Although, a direct connection between ‘Boko Haram’ and the Taliban or al-Qaeda is not discern-able, like its extremist counterparts, ‘Boko Haram’s ideology is based on hostility towards democracy and western anti-Islamic education. Nigeria’s constitution guarantees freedom of religion and the country has a population that is split roughly in half between a Muslim and Christian South. Book Haram has repeatedly stated that it seeks the imposition of a strict Sharia law system throughout Nigeria; currently, nine northern states adhere to Sharia law, with an additional three only marginally implementing it. According to various statements, ‘Boko Haram’ also seeks the abolishment of western-style education, which it states is contrary to the teachings of Islam and its cause. Not much is known about the organizational structure of ‘Boko Haram’. The groups’ founder and former leader, Mohammed Yusuf, was thought to have been highly educated and wealthy. Although, Mohammed Yusuf was killed by security forces in 2009, his deputy, Abubakar Shehu who was initially thought to also have been killed, appeared on a video in 2010 and claimed leadership of the group. Shehu furthermore, threatened fresh attacks against the western influenced Nigerian government. cognitive dissonance theory was adopted. Secondary data were utilized.